2017
DOI: 10.1167/iovs.16-21392
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Met12, a Small Peptide Inhibitor of Fas, on the Retinal Pigment Epithelium and Photoreceptor After Sodium Iodate Injury

Abstract: PurposeA major problem in macular degeneration is the inability to reduce RPE and photoreceptor death. These cells die by necroptosis and apoptosis, respectively, but the upstream activator(s) of these death pathways is unknown. In this study, we use the sodium iodate (NaIO3) model of oxidative stress to test the hypothesis that activation of the Fas receptor contributes to the death of the RPE and photoreceptors.MethodsSodium iodate was injected in Brown-Norway rats via femoral vein injection. Both in vivo (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 34 publications
3
36
1
Order By: Relevance
“…It has been reported that NaIO 3 injury mimicked nonexudative AMD, including the fundus, OCT, and histological characteristics. 13,20,32,33 In addition, the results of this study showed that the retinal blood flow was decreased after the NaIO 3 -induced RPE atrophy, similar to AMD pathology (Fig. 6).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It has been reported that NaIO 3 injury mimicked nonexudative AMD, including the fundus, OCT, and histological characteristics. 13,20,32,33 In addition, the results of this study showed that the retinal blood flow was decreased after the NaIO 3 -induced RPE atrophy, similar to AMD pathology (Fig. 6).…”
Section: Discussionsupporting
confidence: 59%
“…1E). The results of earlier studies have suggested that the NaIO 3 injection induced macrophage accumulation in the retina, 33,44 and the macrophages phagocytose the melanin aggregations. 45 In addition, the expressions of the mRNA transcripts of Il-1b and Il-6, inflammatory cytokines induced from macrophages 46,47 increased at 3 days after the 40 mg/kg NaIO 3 injection (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…This model is likely to prove useful for mechanistic studies addressing the role of TLR9, TLR7, IFN-γ, FasL, type I IFNs, and other immune mediators in CLE and for assessing a variety of therapeutic strategies for the treatment of SLE. Small-molecule FasL inhibitors are under development and have been shown to be highly effective in the blockade of FasL-dependent ocular disorders (73). Related compounds may eventually be appropriate for the treatment of FasLdependent lupus-associated skin disease.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, FasL is upregulated in the skin of CLE, but not psoriasis, patients. Small-molecule FasL inhibitors are under development and have been shown to be highly effective in the blockade of FasL-dependent ocular disorders (73). Related compounds may eventually be appropriate for the treatment of FasLdependent lupus-associated skin disease.…”
Section: Methodsmentioning
confidence: 99%
“… 2 7 NaIO 3 is thought to directly affect the RPE cells with secondary effects on photoreceptors and the CC. It has been shown to induce the production of reactive oxygen species contributing to damage similar to human GA. 8 11 The current models using systemic delivery of NaIO 3 , however, result in widespread degeneration. The degeneration is not succinct and is not surrounded by healthy retina and choroid, as seen in human GA.…”
mentioning
confidence: 99%